HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN TINGKAT AKTIVITAS FISIK DENGAN HANDGRIP STRENGTH PADA MAHASISWA AKTIF FK UPNVJ TAHUN AKADEMIK 2023/2024 - Muhamad Pandji Raihan (2023)
Health concerns about nutritional status are often related to a person's body mass index and physical activity level, so early screening tools are needed as a preventive measure. The adequacy of nutritional status is often evaluated through anthropometry. Some researchers argue that in evaluating nutritional status can use the handgrip strength test. The handgrip strength parameter is a nutritional status assessment model proposed as a screening tool by the American nutrition community (ASPEN). This study aims to determine the relationship between BMI and physical activity level with handgrip strength in active students of FK UPNVJ. The design of this study was cross sectional with random sampling technique using a sample of 55 students as respondents. The results showed that respondents with normal BMI (66.7%) and overweight (69.2%) and moderate (76.9%) and high (70.6%) activity levels had moderate handgrip strength. Based on the results of the fisher exact test, BMI (p = 0.001) and physical activity level (p = 0.001) statistically concluded that there is a significant relationship between BMI and physical activity level with handgrip strength.